The cultural relationship between Fezzan and Tripoli and Cyrenaica during the Islamic ear (Journal of Human Sciences, 2021)
The residents of fzan were interested in cultural life, such as the Libyan territories since lslam and its spread between them they welcomed this religion they accepted the knowledge of his teachings which call for science in most of its verses he became all coming to this religion is willing to learn his science which is Arabic which was the impact on the emergence of a group of scientists in all Libyan regions they have scientific and religious relations that had a role in achieving the cultural among the Libyan regions, the Arabic language has become the official language in Libya since lslam entered into our time it is the language of culture to be the language of religion we do not forget the geographical for Libya, which made it a crossing and stable for many scientists this was causes of cultural growth in Libya this is what l will try to clarify it in this research